Medicine, Madness and Social History
X, 295 p. 8 illus.
Keywords: Written in honour of eminent historian Roy Porter by twenty of his colleagues and students, the collection renders cutting edge scholarship accessible. Historians from the three fields that Porter made his own - the histories of medicine, madness, and the Enlightenment - illustrate his influence while tackling major themes ranging from disability rights to the popularization of science. In their accounts, artisan gardeners jostle with anarchists, dentists, and hypnotists in a lively, and very Porterian, parade.